Preparation method and application of nano-drug carrier
By employing a prepolymerization-coordination-shaping sequence in the preparation process, the problem of balancing structural uniformity, environmental responsiveness, and process scalability of nanomedicine carriers was solved. This resulted in the preparation of nanomedicine carriers with high stability, narrow particle size, and good release behavior, enabling on-demand drug release and efficient cellular uptake.
Patent Information
- Application Number
- CN202511297147.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-11
- Publication Date
- 2025-11-21
- Estimated Expiration
- 2045-09-11
AI Technical Summary
Existing nanomedicine carriers struggle to balance structural uniformity, environmental responsiveness, process scalability, and regulatory friendliness of raw materials and excipients, resulting in issues such as wide particle size distribution, first-dose burst release, protein crown remodeling, high equipment costs, poor batch-to-batch consistency, and significant structural differences.
The preparation process adopts a prepolymerization-coordination-shaping sequence. Chitosan and polyphenols are lightly combined under near-neutral conditions to form uniformly sized nano-co-deposition cores. Then, ferric ions are slowly introduced under the control of a weak chelating agent for uniform coordination. Finally, sodium alginate is introduced and cross-linked with slow-release calcium ions to form a flexible outer layer, which enhances the carrier's anti-dilution ability and anti-protein adsorption performance.
A nanomedicine carrier with high stability, narrow particle size distribution and good release behavior was prepared, which significantly enhanced the morphological stability and colloidal dispersibility of the carrier in complex physiological media, and realized on-demand drug release and efficient cellular uptake.
Smart Images

Figure CN120983368A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of biopharmaceuticals, and particularly relates to a preparation method of a nano-drug carrier and application thereof. BACKGROUND
[0002] Nano-drug carriers are an important research direction in the field of drug delivery in the past two decades. Typical systems include polymeric nanoparticles (such as degradable polyester nanoparticles, polymer micelles, dendrimers), lipid-based carriers (liposomes, solid lipid nanoparticles, lipid nanoparticles), and inorganic and hybrid carriers (mesoporous silica, metal oxides, metal-organic / phenolic coordination networks, etc.). Such carriers can improve the in vivo exposure of poorly soluble or unstable active ingredients, reduce non-target tissue distribution and adverse reactions, and endow the ability to respond to microenvironmental signals such as pH, enzymes, and oxidation-reduction. However, the existing technology still has a difficult trade-off between structural uniformity, environmental responsiveness, process scalability, and regulatory compliance of raw materials.
[0003] From the material aspect, polymeric self-assembled carriers are prepared under organic solvent / anti-solvent conditions, which are prone to have a wide particle size distribution and difficult to inhibit first-dose burst release; the protein corona remodeling of lipid systems occurs in the presence of plasma proteins, and the previously reported active targeting groups are often masked, leading to inconsistent in vivo distribution and in vitro evaluation; although the multi-layer layer-by-layer self-assembly (LBL) strategy can improve the interface, the multiple circulation deposition steps are time-consuming and costly, and the batch consistency is greatly affected by the operator. Metal-polyphenol networks have attracted attention due to their ability to form dense shells under mild conditions and their sensitivity to acidity and competitive ligands, but common one-step rapid mixing often induces cross-particle bridging and uncontrollable precipitation, making it difficult to stably reproduce the shell thickness and pore structure; at the same time, the hydrolysis of metal ions, the deposition of by-products, and the competitive coordination of anions in the buffer system all cause unpredictable structural differences. From the process aspect, many high-performance nano-carriers rely on microfluidic, precision injection, or high-end homogenization equipment to achieve instantaneous mixing and size control, which poses a high threshold for equipment investment and process transfer; when ionically cross-linked polysaccharides (such as alginate-calcium) are used for outer layer stabilization, instantaneous calcium addition often results in uneven shell thickness and rough surface; the lack of process control of the cross-linking front propagation rate makes it difficult to achieve a reproducible balance between dilution resistance and environmental responsiveness. SUMMARY
[0004] In view of the defects of the prior art, the purpose of the present application is to provide a preparation method of a nano drug carrier and its application. In view of the problems of the existing metal-polyphenol carrier, such as easy flocculation, poor stability in body fluid environment and poor release behavior, the present application proposes a preparation process based on the sequence of pre-polymerization-coordination-shaping: first, under near neutral conditions, the mild combination of chitosan and polyphenol is formed to form small particles with uniform size and good dispersity, effectively reducing the adhesion between particles; then, under the regulation of weak chelating agent, slowly introduce trivalent iron ions, make it realize uniform coordination on the surface of the particles, build a dense structure and a responsive inner layer to acidic environment or competitive ligand; finally, introduce sodium alginate and crosslink by slow release of calcium ions to form a flexible outer layer, which cooperates with the inner layer to significantly enhance the anti-dilution capacity and anti-protein adsorption performance of the carrier. Combined with moderate aging and desalting treatment, the metal-polyphenol carrier with high stability, narrow particle size distribution and good release behavior is finally obtained.
[0005] The technical effects of the present application are realized by the following technical scheme: a preparation method of a nano drug carrier, comprising the following steps: S1: chitosan is added to 0.1M glacial acetic acid, and the pH is adjusted to 6-6.5 with NaOH solution to obtain a 0.01-0.05wt% chitosan solution; tannic acid is added to deionized water, and the pH is adjusted to 6-6.5 with acetic acid solution and NaOH solution to obtain a 0.08-0.15wt% tannic acid solution; S2: the chitosan solution and the tannic acid solution of step S1 are mixed in equal volume, a small amount of NaCl is added, and the temperature is kept at 20-25℃ for high-speed shearing treatment, and then the mixture is left to stand for 5min to obtain a nano co-deposition core system; S3: the nano co-deposition core system of step S2 is replaced by dialysis, and the solvent is replaced by 10mM phosphate buffer solution, then 1mM sodium citrate is added to adjust the pH to 6.9-7.1, and 600-800rpm continuous stirring treatment is carried out, at the same time, 1-2mM FeCl3 solution is slowly dropped at a speed of 0.5-1.5mL / min, 0.1M NaOH solution is continuously used to maintain the pH to 6.9-7.1 during the dropping process, and after the dropping is completed, the stirring is continued for 10min to complete the rearrangement; S4: after the treatment of step S3 is completed, 0.03-0.1wt% sodium alginate solution is uniformly added within 10-20min, and the surface adsorption is completed after standing for 5-10min; Ca-EDTA is added to make its final concentration 1-3mM; then the pH is slowly reduced to 6.6-6.8 within 10-15min, and the aging treatment is carried out after standing for 10-30min; S5: after the maturation process of step S4, desalination by dialysis, adjusting pH to 6, then adding 0.01wt% chitosan solution, standing for 5-10min, adding 3-5% trehalose, pre-freezing for 2h at-40℃, drying for 6-12h at-20℃, resolving for 2-4h at 20℃, obtaining the nanodrug carrier; Preferably, in step S2, the amount of NaCl added is 5-15mmol / L; Preferably, in step S2, the high-speed shearing parameters are: rotation speed of 3000-6000rpm, time of 1-2min; Preferably, in step S3, the specific operation of solvent replacement is: 8-14kDa dialysis bag, external liquid volume is 20 times of sample volume, external liquid is 10mM phosphate buffer, replacing external liquid for 3-4 times, each time for 30-60min, maintaining 20-25℃ throughout the process; Preferably, in step S3, the volume ratio of FeCl3 solution to tannic acid solution of step S1 is 10-24:100; Preferably, in step S4, the dropwise addition amount of sodium alginate solution is 100mL / L; Preferably, in step S5, the desalination by dialysis parameters are: 8-14kDa dialysis bag, external liquid volume is 20 times of sample volume, first replacing with 10mM phosphate buffer as external liquid for 1-2 times, then replacing with deionized water containing 5% trehalose as external liquid for 2-3 times, each time for 30-60min, maintaining 20-25℃ throughout the process; Preferably, in step S5, the addition amount of chitosan solution is 20-40mL / L.
[0006] Preferably, another aspect of the present application is to provide an application of the nanodrug carrier, specifically, the drug carrier is preferably suitable for oral administration application; as an application embodiment, the required loaded drug can be directly added in step S2, and co-deposited with the chitosan solution and the tannic acid solution; the outer layer of alginate-calcium ion network maintains colloidal integrity in gastric acid and inhibits early leakage, after entering the intestinal segment, the inner layer of metal-polyphenol coordination bond gradually loosens with the increase of pH and the action of competitive ligands such as bile salts / citrate, realizing on-demand release; the non-covalent interaction of the thin layer of chitosan and the mucus chain enhances the adhesion and residence of intestinal mucosa, promotes permeation and smoothes the initial release.
[0007] The beneficial effects of the present application are as follows: Compared with the prior art, the structure and function of the nano drug carrier prepared by the application are based on multi-level interaction between materials and multi-level synergistic construction in technology. Firstly, under weak acid to near neutral conditions, the application forms a size-limited co-deposition core through hydrogen bonding, hydrophobic interaction and π-π stacking between chitosan and polyphenol molecules; the limited size core localizes the subsequent metal coordination reaction space, significantly reduces the bridging and amorphous aggregation tendency between particles, and makes the coordination growth process under the joint regulation of geometric constraints and diffusion boundaries from the beginning, laying a foundation for finally obtaining a carrier structure with narrow distribution and high repeatability. Subsequently, the introduction of trivalent iron ions with activity regulated by a weak chelating agent in the buffer system triggers the directional coordination crosslinking of polyphenol sites; among them, the weak chelating agent can effectively reduce the activity of free metal ions, prolong the effective reaction time, and promote the metal ions to preferentially deposit in the core-shell interface rich in polyphenol rather than rapidly hydrolyze in the bulk or cross-link between particles. At the same time, the constant acid-base environment inhibits side reactions such as hydroxyl precipitation, and promotes the continuous densification of the coordination network from the inside out, and the metal-polyphenol layer formed has dynamic reversible characteristics, and its bonding energy is sensitive to pH and competitive ligands, so as to realize threshold response regulation of carrier permeability and construction of programmable release channels at the molecular level. Outside the metal-polyphenol layer, a second polysaccharide network is constructed by physical adsorption of alginate and subsequent calcium ion slow-release crosslinking; a segmented calcium ion addition strategy is adopted to control the advancing rate of the crosslinking front, avoiding uneven shell thickness and pore distribution caused by instantaneous crosslinking; the ion crosslinking outer layer and the inner coordination network are complementary in mechanics and permeation behavior; the inner layer gives the carrier skeleton strength and chemical response reversibility, and the outer layer provides resistance to dilution, protein adsorption and interface stability. The energy dissipation interface formed between the two layers through hydrogen bonding and electrostatic adsorption significantly enhances the morphological stability and colloidal dispersibility of the carrier in complex physiological media. In the later maturation stage, the metal-polyphenol complex undergoes site exchange and pore reconstruction under near-steady-state conditions, effectively reducing local stress and structural defects, and further converging the differences between particles; at the same time, the outer layer of polysaccharide segments is rearranged and homogenized under the driving of ion migration, thereby relieving the structural heterogeneity of the carrier as a whole across scales. BRIEF DESCRIPTION OF DRAWINGS
[0008] Figure 1 The cell toxicity test results of the drug carriers of examples 1-3 and comparative examples 1-4 of the application at a concentration of 50 μg / mL; Figure 2 The cell toxicity test results of the drug carriers of examples 1-3 and comparative examples 1-4 of the application at a concentration of 200 μg / mL; Figure 3 The conventional stability test results of the drug carriers of examples 1-3 and comparative examples 1-4 of the application; Figure 4The results of the accelerated stability test of the drug carriers of Examples 1-3 and Comparative Examples 1-4 of the present application; Figure 5 The results of the cell uptake rate test of the drug carriers of Examples 1-3 and Comparative Examples 1-4 of the present application at a concentration of 50 μg / mL; Figure 6 The results of the cell uptake rate test of the drug carriers of Examples 1-3 and Comparative Examples 1-4 of the present application at a concentration of 200 μg / mL; Figure 7 The UV-Vis absorption spectrum of each stage in the preparation process of the drug carrier of Example 1 of the present application. DETAILED DESCRIPTION
[0009] The technical solutions of the present application will be described in detail below with reference to the embodiments of the present application. Obviously, the described embodiments are only some of the embodiments of the present application, not all the embodiments; unless otherwise specified, the raw materials involved in the present application are purchased through conventional commercial channels; the experimental methods without specific conditions are conventional methods and conventional conditions familiar to the field, or according to the conditions recommended by the instrument manufacturer.
[0010] Example 1: A preparation method of a nano-drug carrier, comprising the following steps: S1: 0.15 g of chitosan is added to 500 mL of 0.1 M glacial acetic acid, and the pH is adjusted to 6.3 with NaOH solution to obtain a 0.03 wt% chitosan solution; 0.6 g of tannic acid is added to 500 mL of deionized water, and the pH is adjusted to 6.3 with acetic acid solution and NaOH solution to obtain a 0.12 wt% tannic acid solution; S2: The chitosan solution and the tannic acid solution of step S1 are mixed in equal volumes, and 10 mmol of NaCl is added; the temperature is kept at 22°C for high-speed shearing treatment, the speed is 4500 rpm, the time is 1.5 min, and the standing time is 5 min to obtain a nanocomposite deposition core system; S3: The nanocomposite deposition core system of step S2 is replaced by dialysis, and the solvent is replaced with 10 mM phosphate buffer; the dialysis bag is 12 kDa, the volume of the external liquid is 20 times the volume of the sample, the external liquid is 10 mM phosphate buffer, and the external liquid is replaced for 3 times, each time for 45 min, and the whole process is maintained at 22°C; then 1 mM sodium citrate is added to adjust the pH to 7, and 700 rpm continuous stirring treatment is carried out, while 120 mL of 1 mM FeCl3 solution is slowly added at a speed of 0.8 mL / min, 0.1 M NaOH solution is continuously used to maintain the pH to 7 during the addition process, and after the addition is completed, the stirring is continued for 10 min to complete the rearrangement; S4: After the treatment of step S3 is completed, 100 mL of 0.06wt% sodium alginate solution is added uniformly within 15 min, and surface adsorption is completed after standing for 8 min; 2 mmol of Ca-EDTA is added, and then the pH is slowly reduced to 6.7 within 12 min, and standing for 20 min for curing treatment; S5: After the curing treatment of step S4 is completed, desalination is performed by dialysis, a 12kDa dialysis bag is used, the volume of the external liquid is 20 times the volume of the sample, 10mM phosphate buffer is used as the external liquid for 1 replacement, and then deionized water containing 5% trehalose is used as the external liquid for 2 replacements, each for 45 min, and the whole process is maintained at 22°C; the pH is adjusted to 6, then 30 mL of 0.01wt% chitosan solution is added, and standing for 8 min, 4% trehalose is added, pre-frozen at -40°C for 2h, dried at -20°C for 10h, and resolved at 20°C for 3h to obtain a nano-drug carrier.
[0011] Example 2: A method for preparing a nano-drug carrier, comprising the following steps: S1: Chitosan is added to 0.1M glacial acetic acid, and the pH is adjusted to 6.5 with NaOH solution to obtain a 0.05wt% chitosan solution; tannic acid is added to deionized water, and the pH is adjusted to 6.5 with acetic acid solution and NaOH solution to obtain a 0.15wt% tannic acid solution; S2: The chitosan solution and the tannic acid solution of step S1 are mixed in equal volumes, and a small amount of NaCl is added to make the final concentration 15mmol / L; high-speed shearing treatment is performed at a temperature of 20°C, the rotation speed is 6000rpm, the time is 2min, and standing for 5min to obtain a nano-co-deposition core system; S3: The nano-co-deposition core system of step S2 is replaced by dialysis, and the solvent is replaced with 10mM phosphate buffer, a 14kDa dialysis bag is used, the volume of the external liquid is 20 times the volume of the sample, the external liquid is 10mM phosphate buffer, and the external liquid is replaced 4 times, each for 60min, and the whole process is maintained at 20°C; then 1mM sodium citrate is added to adjust the pH to 7.1, and 800rpm continuous stirring treatment is performed, while 50mL of 2mM FeCl3 solution is slowly added at a speed of 1.5mL / min, 0.1M NaOH solution is continuously used to maintain the pH to 7.1 during the addition process, and stirring is continued for 10min after the addition is completed to complete the rearrangement; S4: After the treatment of step S3 is completed, 100 mL of 0.06wt% sodium alginate solution is added uniformly within 15 min, and surface adsorption is completed after standing for 8 min; 2 mmol of Ca-EDTA is added, and then the pH is slowly reduced to 6.7 within 12 min, and standing for 20 min for curing treatment; S5: After the maturation treatment of step S4, dialysis desalination, 14kDa dialysis bag, the volume of the outer liquid is 20 times the volume of the sample, first use 10mM phosphate buffer as the outer liquid to do 2 times replacement, then use deionized water containing 5% trehalose as the outer liquid to do 3 times replacement, 60min each time, maintain 20℃ throughout the process; adjust the pH to 6, then add 40mL 0.01wt% chitosan solution, stand for 10min, add 5% trehalose, pre-freeze at-40℃ for 2h, dry at-20℃ for 12h, resolve at 20℃ for 4h, obtain the nanodrug carrier.
[0012] Example 3: A preparation method of a nanodrug carrier, comprising the following steps: S1: chitosan is added into 0.1M glacial acetic acid, and NaOH solution is used to adjust the pH to 6 to obtain a 0.01wt% chitosan solution; tannic acid is added into deionized water, and acetic acid solution and NaOH solution are used to adjust the pH to 6 to obtain a 0.08wt% tannic acid solution; S2: equal volume of the chitosan solution and the tannic acid solution of step S1 are mixed, and a small amount of NaCl is added to make the final concentration 5mmol / L; high-speed shearing treatment is carried out at a temperature of 25℃, the rotation speed is 3000rpm, the time is 1min, and the standing time is 5min to obtain a nanoco-deposition core system; S3: the nanoco-deposition core system of step S2 is replaced by dialysis, and the solvent is replaced by 10mM phosphate buffer solution, 8kDa dialysis bag, the volume of the outer liquid is 20 times the volume of the sample, the outer liquid is 10mM phosphate buffer solution, the outer liquid is replaced for 3 times, 30min each time, and the whole process is maintained at 25℃; then 1mM sodium citrate is added to adjust the pH to 6.9, and 600rpm continuous stirring treatment is carried out, while 80mL 1.5mM FeCl3 solution is slowly dropped at a speed of 0.5mL / min, 0.1M NaOH solution is continuously used to maintain the pH to 6.9 during the dropping process, and after the dropping is completed, the stirring is continued for 10min to complete the rearrangement; S4: after the treatment of step S3 is completed, 100mL 0.03wt% sodium alginate solution is uniformly added within 10min, and the surface adsorption is completed after standing for 5min; 1mmol Ca-EDTA is added, then the pH is slowly reduced to 6.6 within 10min, and the maturation treatment is completed after standing for 10min; S5: After the maturation treatment of step S4, desalination is performed by dialysis, 8 kDa dialysis bag, the volume of the outer liquid is 20 times the volume of the sample, first use 10 mM phosphate buffer as the outer liquid to do 1 replacement, then use deionized water containing 5% trehalose as the outer liquid to do 2 replacements, each for 30 min, the whole process is maintained at 25°C; adjust the pH to 6, then add 20 mL of 0.01wt% chitosan solution, stand for 5 min, add 3% trehalose, pre-freeze at -40°C for 2 h, dry at -20°C for 6 h, and resolve at 20°C for 2 h to obtain the nanodrug carrier.
[0013] Comparative Example 1: The operation process of Comparative Example 1 and Example 1 is basically the same, the main difference is that Comparative Example 1 removes the high-shear co-deposition treatment in step S2, and only uses equal volume mixing and magnetic stirring to form the co-deposition core; the remaining operation parameters remain unchanged.
[0014] Comparative Example 2: The operation process of Comparative Example 2 and Example 1 is basically the same, the main difference is that Comparative Example 2 does not perform system buffer conditioning treatment in step S3, that is, the system obtained in step S2 is not replaced with 10 mM phosphate buffer, but the subsequent sodium citrate addition and FeCl3 slow dripping are directly carried out in the original system; the remaining operation parameters remain unchanged.
[0015] Comparative Example 3: The operation process of Comparative Example 3 and Example 1 is basically the same, the main difference is that Comparative Example 3 does not add sodium citrate as a weak chelating rate controller in step S3, and directly slowly drips FeCl3 to complete coordination densification; the remaining operation parameters remain unchanged.
[0016] Comparative Example 4: The operation process of Comparative Example 4 and Example 1 is basically the same, the main difference is that Comparative Example 4 removes Ca-EDTA in step S4, does not perform any calcium ion crosslinking, and retains the alginic acid adsorption to directly enter the subsequent steps of desalination, surface fine-tuning and freeze-drying; the remaining operation parameters remain unchanged.
[0017] Performance test: Cytotoxicity test: The drug carrier samples prepared in Examples 1-3 and Comparative Examples 1-4, together with the medium negative control and blank wells of "nanocarrier + detection system but no cells" (used to eliminate particle background absorption / scattering interference), are evenly distributed in 96-well plates with 6 wells per group of samples; select HT-29 epithelial cells, culture in DMEM containing 10% fetal bovine serum to the logarithmic phase, dilute the cells to 1×10 5After inoculating with 50 μL of the sample at a concentration of 100 cells / mL, the cells were incubated at 37°C and 5% CO2 for 24 h. Then, 50 μL of different concentrations of carrier (50 μg / mL carrier solution; 200 μg / mL carrier solution) were added, and incubation continued for 24 h and 48 h. Cell viability was detected using the CCK-8 assay, with a microplate reader at 570 nm and 630 nm as a reference to subtract the background. Cell viability (%) was calculated as [sample well (subtracted background) OD / control group (subtracted background) OD] × 100%. Each sample was tested at least three times independently, and the average results were taken. Figure 1 and Figure 2 As shown.
[0018] based on Figure 1 and Figure 2 The results showed that the drug carrier prepared in the embodiments of the present invention exhibited high cell viability at both 50 μg / mL and 200 μg / mL concentrations, demonstrating excellent biocompatibility. Based on the results of Comparative Example 1 and Example 1, it can be seen from the results of Comparative Example 1 that after canceling the high-shear co-deposition in step S2, Comparative Example 1 showed poor cell viability, and the difference was greater with time and high concentration conditions. This may be because the nuclei formed by relying solely on equal volume mixing and magnetic stirring lack sufficient geometric constraints and energy input, resulting in larger primary nuclei and wider distribution, which leads to a higher probability of cross-particle bridging and local shell inhomogeneity in the subsequent coordination stage. Based on the analysis of the results of Comparative Example 2 and Example 1, Comparative Example 2 exhibited extremely poor cell viability. This may be due to the direct addition of an iron source and a weak chelating agent to the original system without adjusting the buffer system, leading to drastic changes in ionic strength and pH. This triggered partial metal hydrolysis and non-directional cross-linking in the bulk phase, weakening the selective coordination at the polyphenol enrichment interface. In a serum environment, this type of network is more easily disturbed by protein substitution and ion fluctuations, resulting in a more significant decrease in cell compatibility over time and dosage, and exacerbating the curve fluctuations. Based on the analysis of the results of Comparative Example 3 and Example 1, the cell viability of Comparative Example 3 showed a greater degree of deterioration and dispersion at high concentrations and during the 48-hour period. This may be due to the excessively high iron ion activity and short effective reaction time after omitting weak chelating rate modulators such as citric acid, resulting in a significantly increased coordination rate. This triggered the formation of an excessively cross-linked layer with cross-particle bridging and rapid densification, lacking uniform channels and site rearrangement time, and leaving many uncoordinated metal sites and stress concentration areas inside. Based on the analysis of the results of Comparative Example 4 and Example 1, there was no significant difference between Comparative Example 4 and Example 1 under low and medium doses and 24h conditions. However, the cell viability fluctuated more when the concentration was high and the incubation was extended to 48h. This may be because only Ca-EDTA was removed while alginate adsorption was retained. The outer soft shell lacked a uniform and controllable ionic cross-linking network. The surface polysaccharides were more easily replaced or locally loosened under salt dilution and protein competition, making it difficult to form a stable energy dissipation interface with the inner dynamic coordination layer.
[0019] Stability test: Examples 1-3 and Comparative Examples 1-4 were divided into final administration medium, stored at 4°C, 65% RH, and sampled at 0th month, 1st month, 2nd month, 3rd month and 6th month, respectively; another set of accelerated conditions 40°C, 75% RH, sampled at 0th week, 2nd week, 4th week and 8th week, respectively, each time sampling to detect drug encapsulation rate, the results are shown in Figure 3 and Figure 4 .
[0020] Based on Figure 3 and Figure 4 analysis, the drug carrier prepared in the examples of the present application shows a slow and stable downward trend in encapsulation rate under normal and accelerated conditions, and overall shows excellent stability. Based on the analysis of the results of Comparative Example 1 and Example 1, the encapsulation rate of Comparative Example 1 decreases significantly throughout the entire time period, which may be due to the lack of sufficient geometric constraints and energy input after canceling high shear co-deposition, resulting in larger primary core size and wider distribution; Subsequent coordination stage is more prone to inter-particle bridging and non-uniform splicing of shell thickness / pore, forming more early-stage permeation defect sites; As the storage time increases and the temperature rises, the dynamic coordination network exchanges sites and locally rearranges along these defect paths, accelerating the leakage flux. Based on the analysis of the results of Comparative Example 2 and Example 1, the encapsulation rate of Comparative Example 2 deteriorates most significantly under normal and accelerated conditions, which may be due to the lack of buffer system adjustment, directly adding iron source and weak chelating agent in the original system, causing a sharp change in ionic strength and pH, triggering partial metal hydrolysis and non-directional crosslinking in the bulk phase, weakening the selective coordination of polyphenol-rich interface and trapping impurities; As time and thermal-humidity stress accumulate, site exchange and pore expansion are more likely to occur, leading to rapid decrease in encapsulation rate. Based on the analysis of the results of Comparative Example 3 and Example 1, Comparative Example 3 shows a non-linear, accelerated encapsulation rate decay in the middle and late stages and under accelerated conditions, which may be due to the omission of weak chelating retarder such as citric acid, resulting in excessive activity of iron ions and excessive coordination rate, forming an over-dense and lack-of-uniform-pore coordination layer; Internal stress and insufficiently coordinated metal sites become the initiation centers of micro-cracks and micropores during storage, and dynamic rearrangement preferentially occurs along the defects, temperature rise and humidity promote chain segment migration and coordination exchange, significantly increasing the permeation flux and the deterioration of encapsulation rate in the later stage. Based on the analysis of the results of Comparative Example 4 and Example 1, Comparative Example 4 shows no significant difference from the example in the early stage and low stress condition, but the encapsulation rate decreases gradually under long-term and accelerated conditions, which may be due to the removal of Ca-EDTA and the retention of alginic acid adsorption, the lack of uniform and controllable ionic crosslinking network in the outer layer, and the difficulty in forming a stable energy dissipation interface with the dynamic coordination layer in the inner layer; The surface polysaccharide is easily replaced by environmental ions or locally loose, and the shell permeation resistance decreases with time.
[0021] Cell uptake rate: Caco-2 cells were resuscitated and cultured to differentiate into mature cells, then inoculated into 96-well plates (1 x 10 5 cells / well) and cultured for 24 h; the drug carrier samples prepared by the carrier working solutions of Examples 1-3 and Comparative Examples 1-4 (containing 10% serum, 50 μg / mL carrier solution; 200 μg / mL carrier solution) were configured, and negative control (blank) and positive control (cationic liposome) were added to each well at 100 μL, with 6 wells in each group; incubation was carried out at 37°C, 5% CO2 for 0.5 h, 2 h, 6 h and 24 h, respectively, and the end point was washed with PBS, after eliminating surface adhesion, the fluorescence intensity was quantified by flow cytometry, and the internalization localization was observed by confocal microscopy on a parallel plate, the cell uptake efficiency was measured and analyzed by flow cytometry, and the test results are shown in Figure 5 and Figure 6 .
[0022] Based on Figure 5 and Figure 6Result analysis, the carrier prepared in Example 1 presents a smooth, monotonous rising cell uptake curve with time and dose in serum-containing environment, with less fluctuation. Based on the result analysis of Comparative Example 1 and Example 1, the amplification range of cell uptake rate of Comparative Example 1 deteriorates obviously, with larger fluctuation curve; this may be due to the removal of high shear co-deposition, resulting in the lack of sufficient geometric constraint and transient energy input for the formation of primary nucleus, the nucleus size being too large and the distribution being wide, the chitosan-polyphenol phase density and composition being non-uniform, and this non-uniformity being further transferred to the subsequent coordination stage, causing cross-particle bridging and uneven shell thickness distribution. Based on the result analysis of Comparative Example 2 and Example 1, the amplification range of cell uptake rate of Comparative Example 2 is the smallest, which may be due to the fact that no buffer conditioning is performed, and the iron source and weak chelating agent are directly added in the original system, introducing transient ion strength and pH change, part of the iron ions hydrolyzing and non-directionally combining with the polyphenol, producing heterogeneous or non-uniform coordination domains, weakening the selectivity of the polyphenol enrichment interface and the in-out densification trend, resulting in poor shell structure continuity, decreased protein crown stability, enhanced reversible competition, and further leading to the difficulty of the cell surface receptors in forming effective clusters and persistent contact. Based on the result analysis of Comparative Example 3 and Example 1, the cell uptake rate of Comparative Example 3 improves slowly in the early and middle stages, and the overall amplification range deteriorates obviously, which may be due to the fact that the omission of the weak chelating retarder such as citric acid leads to high iron ion activity and fast coordination rate, and a dense but lack of uniform microporous rapid coordination layer is formed in a short time; this structure releases the internal stress slowly and exchanges the sites during the culture process, causing the surface rigidity to increase, the permeability to decrease, the membrane bending and wrapping to be more dependent on high-energy events, and thus the endocytosis efficiency to be inhibited. Based on the result analysis of Comparative Example 4 and Example 1, the cell uptake rate of Comparative Example 4 is less different from that of Example at a short time point and low dose, but the difference is more obvious after the time is prolonged and the dose is increased; this may be due to the fact that only Ca-EDTA is removed and the alginate adsorption is retained, and the outer layer lacks a uniform and controllable ionic crosslinking network, so that the soft shell is more likely to undergo ion replacement and protein crown remodeling under serum-containing conditions, resulting in loose outer layer structure and unstable surface electric property, the inner layer still having reversible coordination characteristics, but the outer layer being insufficient in buffering dilution and shear, so that the particle residence and effective contact time in the microenvironment around the cells are shortened, and the receptor-mediated and clathrin-coated pit formation are interfered.
[0023] Spectrum test: through UV-Vis spectrum test, the UV-Vis absorption curve of the drug carrier prepared in Example 1 at the corresponding product of each preparation step is determined and plotted, and it should be noted that one aliquot of the sample after S4 is completed is taken, changed to 10 mM citric acid / sodium citrate buffer, the pH is adjusted to 5.3, and the UV-Vis is measured immediately after standing at 25°C for 10 min. The test results are shown in Figure 7 .
[0024] Based on Figure 7The results analysis, S2 co-deposition nuclear curve, UV region in 300-360nm appear strong, slightly broad polyphenol absorption, visible region basically close to the baseline, only a slight baseline uplift, this stage has not formed iron-polyphenol coordination network and mainly with colloidal scattering; FeCl3 base curve, corresponding to near ultraviolet weak and wide absorption band, visible region almost no characteristic peak, used as metal salt background reference; with the step S3 slowly drop Fe 3+ and maintain near neutral pH, drop about 5min in 540-580nm region appear wide shoulder peak, indicating ligand to metal charge transfer band began to form, coordination network in the initial growth stage; further drop to 15min, visible region main band significantly enhanced and to long wave to about 580-620nm, while the peak shape becomes full, reflecting polyphenol deprotonation and coordination number to promote, by the process of in-grain to the outside of the densification; encounter acid trigger, curve shows visible region main band significantly attenuated and slightly back, UV polyphenol band relative to rise, indicating metal-polyphenol complexation occurs reversible loose, in line with the carrier in the acidic environment open permeability and release mechanism. Overall, the curve in the UV segment of the intersection position remains relatively stable, and no significant scattering uplift with time, indicating weak chelation deceleration and pH control to avoid cross-particle bridging and side phase precipitation.
[0025] While embodiments of the application have been shown and described, it is to be understood that the embodiments described are merely exemplary of the principles and application of the present application. Numerous modifications and adaptions can be made without departing from the spirit and scope of the present application, which is defined by the following claims and their equivalents.
Claims
1. A method for preparing a nanomedicine carrier, characterized by, It comprises the following steps: S1: adding chitosan into glacial acetic acid, adjusting pH with NaOH solution to obtain a chitosan solution; adding tannic acid into deionized water, adjusting pH with acetic acid solution and NaOH solution to obtain a tannic acid solution; S2: mixing the chitosan solution and the tannic acid solution of step S1 by equal volume, adding a small amount of NaCl, maintaining a certain temperature for high-speed shearing treatment, standing to obtain a nano co-deposition core system; S3: replacing the solvent of the nano co-deposition core system of step S2 with phosphate buffer solution by dialysis, then adding sodium citrate to adjust pH, continuously stirring, and slowly dropping FeCl3 solution, continuously using NaOH solution to maintain pH during the dropping process, and continuing to stir to complete rearrangement after the dropping is completed; S4: after the treatment of step S3 is completed, uniformly dropping sodium alginate solution, standing to complete surface adsorption; adding Ca-EDTA, then slowly reducing pH, and standing for maturation treatment; S5: after the maturation treatment of step S4 is completed, desalting by dialysis, adjusting pH, then adding chitosan solution, standing, adding trehalose, pre-freezing, drying, and resolving to obtain a nano drug carrier.
2. The method of claim 1, wherein the method is characterized by, In step S2, the amount of NaCl added is 5-15 mmol / L.
3. The method of claim 2, wherein the method further comprises the step of: (d) adding a linker to the surface of the nanoparticles. In step S2, the high-speed shearing parameters are: rotation speed 3000-6000 rpm, time 1-2 min.
4. The method for preparing a nanomedicine carrier according to claim 3, characterized in that, In step S3, the specific operation of the solvent replacement is: 8-14 kDa dialysis bag, the volume of the outer liquid is 20 times the volume of the sample, the outer liquid is 10 mM phosphate buffer, the outer liquid is replaced 3-4 times, each time for 30-60 min, and the whole process is maintained at 20-25℃.
5. The method for preparing a nanomedicine carrier according to claim 4, characterized in that, In step S3, the volume ratio of the FeCl3 solution to the tannic acid solution of step S1 is 10-24:
100.
6. The method for preparing a nanomedicine carrier according to claim 5, characterized in that, In step S4, the dropping amount of the sodium alginate solution is 100 mL / L.
7. The method for preparing a nanomedicine carrier according to claim 6, characterized in that, In step S5, the dialysis desalting parameters are: 8-14 kDa dialysis bag, the volume of the outer liquid is 20 times the volume of the sample, first using 10 mM phosphate buffer as the outer liquid to replace 1-2 times, then using deionized water containing 5% trehalose as the outer liquid to replace 2-3 times, each time for 30-60 min, and the whole process is maintained at 20-25℃.
8. The method for preparing a nanomedicine carrier according to claim 7, characterized in that, In step S5, the amount of chitosan solution added is 20-40 mL / L.
9. The nano drug carrier according to any one of claims 1-8 for use in oral drug carriers.
Citation Information
Patent Citations
pH response type tannic acid / chitosan nanometer capsules and preparation method thereof
CN110227069A
Chitosan interface modified ellagic acid nanostructure lipid carrier and preparation method thereof
CN117398294A
Tannin-chitosan composites
US20110059162A1
Cited By
Salt-containing probiotic composition and preparation method thereof
CN121652971A
A salt-containing probiotic composition and a method for preparing the same
CN121652971B